Alchemy and Creation in the Work of Albertus Magnus - Rinotas, Athanasios (Conatus - Journal of Philosophy, 2019)
Albertus Magnus’ alchemy is a subject that has attracted the attention of the scholars since the early decades of the 20th century. Yet, the research that has been conducted this far is characterised by its non philosophical character. As a matter of fact, the previous studies approached Albertus’ alchemy either in terms of history of science or of intellectual history. In this paper, I focus on Albertus’ definition of alchemical transmutation that is found in his De mineralibus and I analyze it in terms of his theory of creation and of his theory of matter. Therefore, I show whether a re-creation of a metal is in accordance with Albertus’ philosophy and congruently I bring forth the Aristotle Graecus and the Aristotle Latinus that are found as background in his alchemical theory of transmutation. Ultimately this paper aims to show that the aforementioned theory is not an arbitrary statement from Albertus’ part, but the result of a serious philosophical endeavour.